RAPORTUL DINTRE STAT ŞI RELIGIE ÎN CONDIŢIILE TRANZIŢIEI - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2009)
In this article the research is based on the report between state and religion put in transition conditions. It is emphasized that the state must built this report proceeding from the fact that the religious cults are autonomous, separated from the state, equal in rights in front of the law and public authorities. It has also to respect the non-interference principle of the state, concerning religion problems, because the tendency of transforming the orthodoxy in a dominant one becomes obvious. At the same time, it is pointed out that the occultist religions and totalitarian sects are an impending danger which represses the personality of human being, using the proselytism in order to change the consciousness and its liberty.